Exercise Factors Released by the Liver, Muscle, and Bones Have Promising Therapeutic Potential for Stroke - Stephan, Joseph S.; Sleiman, Sama F. (Frontiers in Neurology, 2021)
Stroke is one of the leading causes of death and disability in the world. Stroke not only affects the patients, but also their families who serve as the primary caregivers. Discovering novel therapeutic targets for stroke is crucial both from a quality of life perspective as well as from a health economic perspective. Exercise is known to promote neuroprotection in the context of stroke. Indeed, exercise induces the release of blood-borne factors that promote positive effects on the brain. Identifying the factors that mediate the positive effects of exercise after ischemic stroke is crucial for the quest for novel therapies. This approach will yield endogenous molecules that normally cross the blood brain barrier (BBB) and that can mimic the effects of exercise. In this minireview, we will discuss the roles of exercise factors released by the liver such as beta-hydroxybutyrate (DBHB), by the muscle such as lactate and irisin and by the bones such as osteocalcin. We will also address their therapeutic potential in the context of ischemic stroke.